FAKTOR - FAKTOR YANG MEMPENGARUHI KEBERHASILAN USAHA PENGEPUL SAMPAH DI KOTA YOGYAKARTA - Saputra, Adi; Mulasari, Surahma Asti (Optimum: Jurnal Ekonomi dan Pembangunan, 2015)
This was an observational analytical research with a cross-sectional design. The research subjects were 39 rubbish scavengers. A bivariate analysis result showed that there was an influence of a working motivation towards a business success, there was no influence of business experience towards a business success, and there was an influence of an educational level towards a business success. There was an influence of a working motivation towards a business success, no influence of a business experience towards a business success, and there was an influence of an educational level toward a business success.